Study Of E-Learning For The Workplace In Malaysia - Yang, You (2004)
Forward-thinking Malaysian employers are starting to embrace e-learning to become more productive and innovative, regardless of the size, resources or sector of their organization. At the same time, they are using e-learning to create self-directed, lifelong learners among their employees--and to save money. E-learning delivers content through electronic information and communications technologies. (ICTs).